Conducting clinical genomics research during the COVID‐19 pandemic: Lessons learned from the CSER consortium experience. Issue 2 (7th November 2022) - Kraft, Stephanie A.; Russell, Heidi; Bensen, Jeannette T.; Bonini, Katherine E.; Robinson, Jill O.; Sahin‐Hodoglugil, Nuriye; Renna, Kathleen; Hindorff, Lucia A.; Kaufman, Dave; Horowitz, Carol R.; Waltz, Margaret; Zepp, Jamilyn M.; et al.
Abstract: Clinical research studies have navigated many changes throughout the COVID‐19 pandemic. We sought to describe the pandemic′s impact on research operations in the context of a clinical genomics research consortium that aimed to enroll a majority of participants from underrepresented populations. We interviewed (July to November 2020) and surveyed (May to August 2021) representatives of six projects in the Clinical Sequencing Evidence‐Generating Research (CSER) consortium, which studies the implementation of genome sequencing in the clinical care of patients from populations that are underrepresented in genomics research or are medically underserved. Questions focused on COVID′s impact on participant recruitment, enrollment, and engagement, and the transition to teleresearch. Responses were combined and thematically analyzed. Projects described factors at the project, institutional, and community levels that affected their experiences. Project factors included the project′s progress at the pandemic′s onset, the urgency of in‐person clinical care for the disease being studied, and the degree to which teleresearch procedures were already incorporated. Institutional and community factors included institutional guidance for research and clinical care and the burden of COVID on the local community. Overall, being responsive to community experiences and values was essential to how CSER navigated evolving challenges during the COVID‐19 pandemic.